Molecular identification of seed‐feeding flies dissected from herbarium specimens clarifies the 100‐year history of parasitism by Japanagromyza tokunagai in Japan. Issue 2 (9th December 2021) - Yamashita, Yumi; Ogura‐Tsujita, Yuki; Nagata, Nobuaki; Kurosawa, Takahide; Yukawa, Tomohisa
Abstract: Insect pests, particularly seed‐feeding flies, can cause serious damage to the fruits of many wild orchid species. Evidence of fly damage has been observed in 55 orchid species, belonging to 25 genera, distributed throughout Japan. Although some authors suggested that the observed increase in fly damage to orchids in recent years is related to the introduction of exotic species, the timing and route of spread remain unclear. We examined herbarium specimens of seven orchid species, collected between 1923 and 2016, to collect coarctate pupae and empty puparia, with minimal damage to the specimens. Genomic DNA was then extracted from the insect tissue and species were identified using mitochondrial cytochrome oxidase subunit 1 barcode regions. Long amplicons (660 base pairs [bp]) were obtained from 45.2% of samples and short amplicons (162 bp) were obtained from 90.3% of samples. In total, 51 of 62 samples had nucleotide sequences homologous to Japanagromyza tokunagai, with specimens distributed across collection years and geographic locations. Therefore, the severe damage to Japanese orchids observed in recent years is not related to the recent introduction of an exotic species; it may be related to a rapid increase in a native species. This work highlights the value of herbaria as important resources for elucidating the history and distribution of parasitic insects. Abstract : Seed‐feeding fly tissues (coarctate pupa; a, c, or puparium; b, d) were dissected from Japanese orchid fruits specimens kept in herbarium and molecularly identified using 660 bp (a, b) or 162 bp (c, d) amplicon of cytochrome oxidase subunit 1 barcoding region. In total, 51 of 62 samples, collected from 1923 to 2016, were identified as Japanagromyza tokunagai (Diptera: Agromyzidae). Therefore, the severe damage in recent years is not related to the recent introduction of an exotic species. This work also highlights the value of herbaria as important resources for elucidating the history and distribution of parasitic insects.